Student’s higher-order thinking skills and collaboration skills in online learning during pandemic - Adilah Afikah; Eli Rohaeti; Jumadi Jumadi; Riki Perdana (Institute of Advanced Engineering and Science, 2023)
Higher-order thinking skills (HOTS) and collaboration skills are critical for all students, starting from early to senior high school. This study aimed to describe HOTS and collaboration skills in online learning according to gender, type of school, and grade level. This research was descriptive quantitative by explaining and comparing the results of the questionnaires given to students. The respondent of this study was 331 students who were obtained randomly from junior and senior high school in Indonesia. The results showed students’ HOTS in online learning; the mean score of the students was 3.82 (moderate). While collaboration skills, the mean score of the students was 3.95 (moderate); collaboration skills domains are positively related to HOTS. According to gender, type of school, and education level, there was no significant difference between students’ HOTS and collaboration skills. Based on these findings, teachers can teach to maximize learning, even though it was online, to improve HOTS and collaboration skills in online learning. This can also influence the policies to be taken by higher education to equip prospective educators to adjust themselves in providing learning to students in different conditions and situations.